IDEAL RESPONSIBILITY FOR THE PROCUREMENT OF GOVERNMENT GOODS/SERVICES ACCORDING TO THE LEGAL ASPECTS OF STATE ADMINISTRATION - NOVI ACHMAD HARYADI TAMHER (Awang Long Law Review, 2021)
The legal responsibility for implementing government procurement of goods/services carried out by state civiland state administrators should be identified first so that they are included in the responsibility for administrative law, civil law, and criminal law. This is because the legal protection for the responsibility of implementing goods and services procurement has not yet been maximized. Government procurement of goods/services is essentially an effort by service users to obtain or realize the goods/services needed, by using certain methods and processes in order to reach an agreement on price, time, and other agreements based on the values ​​and procedures for the procurement of goods and services in force in the country. the government sector, so that it is in accordance with the state's goal of creating general welfare. Procurement actors must be responsible for their duties and authorities as in the stages in the procurement of government goods/services, accountability in the process of procurement of government goods and services must be carried out by procurement actors involved in the government goods/services procurement process. The legal aspects of the process of procurement of government goods and services in addition to criminal law and civil law, there is also state administrative law. Responsibility is a must for someone to carry out what has been required of him. Meanwhile, according to the law, responsibility is a consequence of the consequences of a person's freedom regarding his actions related to ethics or morals in carrying out an act.